El impacto de la contaminación auditiva en los ciudadanos de la ciudad de Machala, dentro del cuadrante determinado por las siguientes calles Buenasvistas , Boyaca, Avenida las Palmeras y Arízaga, entre los meses de Enero y Abril inclusive, del año 2013 - Guamán Pereira, Manuela del Rocío (2013)
The research is based on the hypothetical-educational processes subject to the scientific method from the empirical analytic paradigm that guides the systematization of the contents of the diagnosis in whose structure the problem of the study is addressed, described, fixed its location and Justifies it.